Correlations between the alpha-Gal antigen, antibody response and calcification of cardiac valve bioprostheses: experimental evidence obtained using an alpha-Gal knockout mouse animal model - Naso, Filippo; Colli, Andrea; Zilla, Peter; Calafiore, Antonio Maria; Lotan, Chaim; Padalino, Massimo A.; Sturaro, Giulio; Gandaglia, Alessandro; Spina, Michele (Frontiers in Immunology, 2023)
Preformed antibodies against αGal in the human and the presence of Gal antigens on the tissue constituting the commercial bioprosthetic heart valves (BHVs, mainly bovine or porcine pericardium), lead to opsonization of the implanted BHV, leading to deterioration and calcification. Murine subcutaneous implantation of BHVs leaflets has been widely used for testing the efficacy of anti-calcification treatments. Unfortunately, commercial BHVs leaflets implanted into a murine model will not be able to elicit an αGal immune response because such antigen is expressed in the recipient and therefore immunologically tolerated. This study evaluates the calcium deposition on commercial BHV using a new humanized murine αGal knockout (KO) animal model. Furtherly, the anti-calcification efficacy of a polyphenol-based treatment was deeply investigated. By using CRISPR/Cas9 approach an αGal KO mouse was created and adopted for the evaluation of the calcific propensity of original and polyphenols treated BHV by subcutaneous implantation. The calcium quantification was carried out by plasma analysis; the immune response evaluation was performed by histology and immunological assays. Anti-αGal antibodies level in KO mice increases at least double after 2 months of implantation of original commercial BHV compared to WT mice, conversely, the polyphenols-based treatment seems to effectively mask the antigen to the KO mice's immune system. Commercial leaflets explanted after 1 month from KO mice showed a four-time increased calcium deposition than what was observed on that explanted from WT. Polyphenol treatment prevents calcium deposition by over 99% in both KO and WT animals. The implantation of commercial BHV leaflets significantly stimulates the KO mouse immune system resulting in massive production of anti-Gal antibodies and the exacerbation of the αGal-related calcific effect if compared with the WT mouse. The polyphenol-based treatment applied in this investigation showed an unexpected ability to inhibit the recognition of BHV xenoantigens by circulating antibodies almost completely preventing calcific depositions compared to the untreated counterpart.